A new biophysics approach using photoacoustic spectroscopy to study the DNA-ethidium bromide interaction - Bugs, M. R.; Cornelio, M. L. (Springer, 2002)
We have examined the binding processes of ethidium bromide interacting with calf thymus DNA using photoacoustic spectroscopy. These binding processes are generally investigated by a combination of absorption or fluorescence spectroscopies with hydrodynamic techniques. The employment of photoacoustic spectroscopy for the DNA-ethidium bromide system identified two binding manners for the dye. The presence of two isosbestic points (522 and 498 nm) during DNA titration was evidence of these binding modes. Analysis of the photoacoustic amplitude signal data was performed using the McGhee-von Hippel excluded site model. The binding constant obtained was 3.4 x 10(8) M(bp)(-1), and the number of base pairs excluded to another dye molecule by each bound dye molecule (n) was 2. A DNA drug dissociation process was applied using sodium dodecyl sulfate to elucidate the existence of a second and weaker binding mode. The dissociation constant determined was 0.43 mM, whose inverse value was less than the previously obtained binding constant, demonstrating the existence of the weaker binding mode. The calculated binding constant was adjusted by considering the dissociation constant and its new value was 1.2 x 10(9) M(bp)(-1) and the number of excluded sites was 2.6. Using the photoacoustic technique it is also possible to obtain results regarding the dependence of the quantum yield of the dye on its binding mode. While intercalated between two adjacent base pairs the quantum yield found was 0.87 and when associated with an external site it was 0.04. These results reinforce the presence of these two binding processes and show that photoacoustic spectroscopy is more extensive than commonly applied spectroscopies.
Keywords: photoacoustic spectroscopy; DNA; Ethidium Bromide; binding modes; dissociation constant